Kenya and Vietnam Ecosystem Services Database: Per Hectare Values - Hettiarachchi, Upeksha; Zhang, Wei (International Food Policy Research Institute, 2022)
The database provides values for ecosystem services in Kenya and Vietnam. The data collected through literature review includes the type of biome, ecosystem service, raw data for the ecosystem service value and the method of ecosystem service value estimation. The variables for which data was collected were based on The Economics of Ecosystems and Biodiversity (TEEB) framework. The TEEB framework allows for the categorization of biomes, sub biomes and types of ecosystem services to be standardized. The ecosystem services are divided into three levels of classification: ecosystem services, ecosystem sub-services and ecosystem sub-sub-services.